Leafie : Ayam buruk rupa dan itik kesayangan / Hwang Sun-mi; Penerjemah, Dwita Rizki Nientyas; Editor, Esti A. Budihapsari - SUN-MI, Hwang; DWITA Rizki Nientyas; ESTI A. Budihapsari (Qanita, 2013)
224 hlm. : Ilus. ; 20,5 cm.